1994
DOI: 10.2105/ajph.84.7.1158
|View full text |Cite
|
Sign up to set email alerts
|

Using a geographic information system to understand child pedestrian injury.

Abstract: Data from police accident reports involving pedestrians less than 20 years of age in Hartford, Conn, during 1988 through 1990 were abstracted and entered into a geographic information system. Two high-frequency collision areas were identified and compared. There were 374 child pedestrians involved in collisions (a rate of 28 per 10,000). Two high-occurrence areas accounted for 30% of collisions. Collisions in one of these areas were more likely to involve younger children (8.1 vs 10.2 years of age) and to occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 15 publications
0
34
0
2
Order By: Relevance
“…The majority of these analyses have been based on ecologic study designs using data grouped within a variety of geographic boundaries including counties, municipalities, zip codes or census tracts. GIS have been used to study a variety of exposures and health outcomes including infectious disease ( Glass et al, 1995 ) , cancer ( Lewis -Michl et al, 1996) , chronic respiratory disease ( English et al, 1999 ), and unintentional injuries ( Braddock et al, 1994;Peek -Asa et al, 2000 ). These studies have capitalized on one of the primary strengths of GIS, the ability to use spatial attributes for linking disparate datasets in the analysis of complex, multivariate outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these analyses have been based on ecologic study designs using data grouped within a variety of geographic boundaries including counties, municipalities, zip codes or census tracts. GIS have been used to study a variety of exposures and health outcomes including infectious disease ( Glass et al, 1995 ) , cancer ( Lewis -Michl et al, 1996) , chronic respiratory disease ( English et al, 1999 ), and unintentional injuries ( Braddock et al, 1994;Peek -Asa et al, 2000 ). These studies have capitalized on one of the primary strengths of GIS, the ability to use spatial attributes for linking disparate datasets in the analysis of complex, multivariate outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some GIS -based health studies have used the individual as the unit of measure by georeferencing subjects to their residence (Braddock et al, 1994;Lewis-Michl et al, 1996;English et al, 1999;Ward et al, 2000 ). From an analytic epidemiologic perspective, analyses at the individual level are preferred due to inherent strengths of case -control and cohort designs in making inferences regarding causality.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of collision involving pedestrian age 17 and younger and 65 and older occurred near home. There is extensive pediatric literature addressing the proximity of child auto-pedestrian collisions to victims' homes or schools [Agran et al, 1994;Malek et al, 1990;Braddock et al, 1994;Roberts et al, 1997;Lightstone et al, 2001;La Scala et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Literature exploring child pedestrian injury suggests that collisions often occur close to children's homes or schools [Agran, Winn, Anderson, 1994;Malek, Guyer, Lescoheir, 1990;Braddock, Lapidus, Cromley, 1994;Roberts et al, 1997;Lightstone, Dhillon, Peek-Asa, 2001;La Scala, Guenewald, Johnson, 2004]. Additionally, past studies have identified factors associated with the risk of adult pedestrian collision and injury such as age and gender [La Scala, Gerber, Gruenewald, 2000;Graham, Glaister, Anderson, 2005;Hijar, Kraus, Tovar, 2001;Gorrie, Brown, Waite, 2008], alcohol involvement [La Scala et al, 2000;Shuurman, Cinnamon, Crooks, 2009;Paulozzi, 2006], and socio-economic status [Rivara and Barber, 1985;La Scala et al, 2000;Graham et al, 2005;Chakravarthy, Anderson, Ludlow, 2010] among others.…”
Section: Introductionmentioning
confidence: 99%
“…GIS is particularly well suited for studying these associations because of its spatial analysis and display capabilities. Recently GIS has been used in the surveillance and monitoring of vector-borne diseases (Glass GE, et al, 1995;Beck LR, et al, 1994;Richards FO, et al,1993;Clarke KC, et al, 1991), water borne diseases (Braddock M, et al,1994), in environmental health (Barnes S and Peck A. 1994;Wartenberg D, et al, 1993;Wartenberg D. et al,1992), and the analysis of disease policy and planning (Marilyn O Ruiz, et al,2004).Spatial analysis function of GIS can be widened and strengthened by using spatial statistical analysis, allowing Spatial Statistical Analysis for the deeper exploration, analysis, manipulation and interpretation of spatial pattern and spatial correlation of the animal disease.…”
Section: Introductionmentioning
confidence: 99%